COVID-19 Infection and Outcomes in Newborn Screening Cohorts of Sickle Cell Trait and Sickle Cell Disease in Michigan and Georgia. Issue 4 (20th May 2023) - Paulukonis, Susan T.; Snyder, Angela; Smeltzer, Matthew P.; Sutaria, Ankit N.; Hurden, Isabel; Latta, Krista; Chennuri, Swathi; Vichinsky, Elliott; Reeves, Sarah L.
Abstract : The sickle cell mutation increases morbidity in those with sickle cell disease (SCD) and potentially sickle cell trait, impacting pulmonary, coagulation, renal, and other systems that are implicated in COVID-19 severity. There are no population-based registries for hemoglobinopathies, and they are not tracked in COVID-19 testing. We used COVID-19 test data from 2 states linked to newborn screening data to estimate COVID outcomes in people with SCD or trait compared with normal hemoglobin. We linked historical newborn screening data to COVID-19 tests, hospitalization, and mortality data and modeled the odds of hospitalization and mortality. Georgia's cohort aged 0 to 12 years; Michigan's, 0 to 33 years. Over 8% of those in Michigan were linked to positive COVID-19 results, and 4% in Georgia. Those with SCD showed significantly higher rates of COVID-19 hospitalization than the normal hemoglobin Black cohort, and Michigan had higher rates of mortality as well. Outcomes among those with the trait did not differ significantly from the normal hemoglobin Black group. People with SCD are at increased risk of COVID-19–related hospitalization and mortality and are encouraged to be vaccinated and avoid infection. Persons with the trait were not at higher risk of COVID-related severe outcomes.